Pentaho Analytics for MongoDB cookbook : over 50 recipes to learn how to use Pentaho Analytics and MongoDB to create powerful analysis and reporting solutions /: over 50 recipes to learn how to use Pentaho Analytics and MongoDB to create powerful analysis and reporting solutions. (2015) - Latino, Joel; Ward, Harris
No abstract available